2019
DOI: 10.1029/2019ef001282
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Anthropogenic CO2 Emissions at City Level Using OCO‐2 Observations: A Global Perspective

Abstract: Satellite observations of anthropogenic carbon dioxide (CO 2 ) emissions within urban settings offer unique potential to understand carbon sources and sinks and evaluate carbon mitigation strategies. Despite availability of column-averaged dry air mole fraction of CO 2 (X CO2 ) from Orbiting Carbon Observatory-2 (OCO-2), temporal variations of X CO2 and their drivers in cities remain poorly understood due to inconsistent definitions of urban extent, diverse urban forms, and unresolved impacts of urban vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The two datasets showed a good correlation with a deter-mined coefficient (R 2 ) of 0.60. Several studies have correlated satellite-based XCO 2 anomalies with CO 2 emissions (Fu et al, 2019;Shekhar et al, 2020). Yang et al (2019) performed a correlation analysis between the GOSAT-based XCO 2 anomalies and the ODIAC CO 2 emissions over China and found a significant correlation with a determined coefficient (R 2 ) of 0.82 which increased up to 0.95 if the analysis was carried out with higher CO 2 emission values.…”
Section: Correlation Analysis Between Oco-2 Xco 2 Anomalies and Odiac Emissionsmentioning
confidence: 99%
“…The two datasets showed a good correlation with a deter-mined coefficient (R 2 ) of 0.60. Several studies have correlated satellite-based XCO 2 anomalies with CO 2 emissions (Fu et al, 2019;Shekhar et al, 2020). Yang et al (2019) performed a correlation analysis between the GOSAT-based XCO 2 anomalies and the ODIAC CO 2 emissions over China and found a significant correlation with a determined coefficient (R 2 ) of 0.82 which increased up to 0.95 if the analysis was carried out with higher CO 2 emission values.…”
Section: Correlation Analysis Between Oco-2 Xco 2 Anomalies and Odiac Emissionsmentioning
confidence: 99%
“…Currently, 85% of the energy in the world comes from fossil fuels such as coal, oil, and natural gas . It is worth noting that an excessive dependence on fossil fuels has led to an energy crisis, and at the same time, the released greenhouse gas CO 2 has caused serious environmental pollution problems. , Thus, how to effectively solve the issues of the energy crisis and environmental pollution has become a worldwide challenge. In this case, conversion of CO 2 to chemical fuels is considered to be one of the most efficient solutions. , However, since CO 2 molecules are exceptionally stable, the complicated conversion process and similar product potentials result in low catalytic efficiency and poor product selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, precipitation, water vapor content [7], and consequently, vegetation cover have a direct effect [8] on the monthly CO 2 concentration fluctuations. example, Falahatkar et al investigated the interaction of land surface temperature and Normalized Difference Vegetation Index with GOSAT XCO 2 data for one year over Iran [27], while Fu et al tracked the fossil fuel consumption in urban areas and revealed the impacts of urban vegetation on seasonal variation of XCO 2 using OCO-2 observations [28]. In addition, Siabi et al assessed the CO 2 distribution over Iran using XCO 2 data from OCO2 during the growing season [29].…”
Section: Introductionmentioning
confidence: 99%